Optimal Design and Modeling of Annular Photocatalytic Wall Reactors - Imoberdorf, Gustavo Eduardo (2007)
The performance of photocatalytic reactors is largely conditioned by their configuration. In particular, photocatalytic wall reactors are affected by configuration-linked factors such as diffusive resistances, reactor radiation incidence and absorption efficiencies, and by the amount of photocatalytic surface area that is effectively irradiated. In this paper, the effect of different configurations and design variables on the performance of annular photocatalytic reactors was analyzed.With this purpose, a complete reactor model was developed and solved, taking into account singleand multi-annular configurations, different reactor dimensions, and three flow patterns. The model was successfully validated against experimental results for the photocatalytic oxidation of perchloroethylene (PCE) in a multi-annular reactor. From the simulation results, it was possible to conclude that the unfavorable effect of the diffusive resistances on the reactor performance could be reduced by constructing photocatalytic annular wall reactors of small annular width and large photocatalytic surface area. Besides, the multi-annular configuration is more effective in using the radiative energy fed into the reactor than the single-annulus reactor configuration. According to the results obtained for PCE photocatalytic degradation, among all the studied reactor configurations the most efficient one is that with its annuli interconnected in a series pattern.